Expeditious Metal-Free Access to Functionalized Polycyclic Acetals under Mild Aqueous Conditions - Kasare, S.; Bankar, S.K.; Ramasastry, S.S.V. (American Chemical Society, 2014)
A facile approach for the synthesis of furopyrans and bicyclic bisacetals under mild aqueous conditions is described. This potentially green, diversity oriented approach involves cascade Michael addition and cycloacetalization of pyranones and 1,3-dicarbonyls. An interesting switch in the product class was observed depending on the type of pyranone employed. Products of type I and II obtained herein are an integral part of several bioactive natural products and medicinally interesting compounds. © 2014 American Chemical Society.
Keywords: Sodium dodecyl sulfate; Organic compounds; Chemical reactions; Pharmaceuticals